Effect of the nature of oil, presence of electrolytes, phase volume ratios and pH of the aqueous phases on the in vitro release of nimesulide from multiple w/o/w emulsions - Tandon P.; Mishra B. (My University, 2025)
In vitro release characteristics of nimesulide encapsulated in internal aqueous phase of w/o/w multiple emulsions were investigated to see the effect of four formulation variables viz. the nature of oil phase, the presence of electrolytes in internal aqueous phase, phase volume ratios and the pH of the aqueous phases. The drug release rates were significantly affected by the above variables. The results indicated that optimization of the above variables is a prerequisite so as to obtain a desired delivery rate of the drug from multiple w/o/w emulsions.